Structural monitoring of a large archaeological wooden structure in real time, post PEG treatment - Collett,H; Bouville,F; Giuliani,F; Schofield,E (Forests, 2021)
Large archaeological wooden structures are potentially at risk of structural failure through deformation and cracking over time if they are left untreated and their structural health is not maintained. This could be in part due to, for example, the shrinkage of waterlogged wood as it dries, or time-dependent creep processes. These dimensional changes are accompanied by associated stresses. However, there are few studies analysing the movement of large wooden structures in real time as they dry, particularly after their conservation treatment. This paper follows the structural monitoring of the Mary Rose from after the conservation treatment, where it was sprayed with polyethylene glycol, through to the ship’s air-drying process and beyond to assess the effects that drying has had on the displacement of the timbers. A laser-based target system was used to collect displacement data between 2013 and 2020 and the data showed a significant slowing of displacement as the drying reached an equilibrium.